Korelasi Implementasi Model Poe Berbasis Inquiri-Humanistik dengan Higher Order Thinking Skill Level I Decision Making pada Praktikum Fisika Dasar - Pratiwi, Umi; Nurhidayati, Nurhidayati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Curriculum 2013 as a curriculum that emphasizes the three domains of learning strongly supports the ability to solve problems. One of the capabilities that must be prepared in this century is the ability of high-level thinking is an important ability as part of the process of problem solving. This study aims to determine the ability of high-level thinking at Level I decision-making stage before entering the stage of problem solving, that is how the correlation of the application of Inquiri-Humanistic POE model (variable x) to the thinking ability of high level I in the decision making stage (variable II). This study uses the application of inquiry-humanistic POE model as a solution in solving the problems faced by physics education students. The subjects of the study used one group of subjects without any comparison, namely the second semester students of physics education courses in the Physics Basic lab course. This research is a pre experimental study of pretest-posttest one-group design supported by qualitative-descriptive approach. The research data is conducted using observation and test of high-order thinking ability (pretest end posttest). The results showed that the application of inquire-humanistic POE model correlated 0.307% to the ability of high level thinking level I in the decision making stage. It is expected that the next level can be measured significantly with the implementation of inquiry-humanistic POE model